REFORMASI SISTEM REKRUTMEN PEGAWAI NEGERI DI KOREA SELATAN - Agus Subagyo (Badan Kepegawaian Negara | The National Civil Service Agency, 2009)
This paper need to descript the system of civil service recruitment that implemented by South Korea for latest 10 years so success to made high quality and performance beureucracy on the frame to endorse economic growth and national development. The system of civil service recruitment that transparent, accountable, and professional success to made a high work culture, power of competitor, and performance so positioning this ginseng’s state as world economic power. The Pillar of government beureucracy that clean, without corruption, colution, and nepotism, endorsed a high discipline and loyality based the meritocracy system is key success South Korea’s economic development. Indonesia must to take learning from the success of South Korea in to managed and pursuit of beureucracy reformacy, especially reformacy of civil service system that based on meritocracy system.Key words: reformacy, recruitment, meritocracy, and performance.